Drugs for HER-2-positive breast cancer - Sibilia, Maria; Zielinski, Christoph C.; Bartsch, Rupert; Grunt, Thomas W.; SpringerLink (Online service). (Basel Springer Basel, 2011)
Growth factor receptors have long been known to drive malignant transformation and cancer progression. The epidermal growth factor receptor (EGFR, ErbB, HER) system is likely the best described membrane receptor tyrosine kinase family in malignant tumors. With implementation of the growth-inhibitory anti-HER-2 antibody trastuzumab (Herceptin) for the treatment of HER-2-positive advanced metastatic breast cancer, a new era has dawned in the therapy of this malignant disease. Unfortunately, trastuzumab-sensitive cancers invariably develop resistance to the antibody after some time. Recent clinical studies have revealed that these refractory tumors are still responsive to inhibition of the HER receptor family using dual HER-1/-2 inhibitors such as lapatinib (Tykerb/Tyverb). Moreover, a multiplicity of novel, improved irreversibly acting small molecular HER tyrosine kinase inhibitors are in the pipeline of many drug developing companies and are being evaluated in the clinical setting.
Drugs for HER-2-positive Breast Cancer: A Major Approval for Translational Cancer Research (Maria Sibilia, Christoph C. Zielinski, Rupert Bartsch, Thomas Grunt) -- The EGFR/ErbB family in breast cancer: from signaling to therapy (Wolfgang J. Köstler and Yosef Yarden) -- Trastuzumab as Adjuvant treatment for early stage HER-2 positive breast cancer (Rupert Bartsch and Guenther G. Steger) -- Trastuzumab Resistance in breast cancer (Floriana Morgillo, Michele Orditura, Teresa Troiani, Erika Martinelli, Ferdinando De Vita, Fortunato Ciardiello) -- Treatment with Trastuzumab beyond Progression (Gunter von Minckwitz and Cristina Pirvulescu) -- Pertuzumab ? a HER-2 dimerisation inhibitor ? for the treatment of breast and other cancers (Giulia Bianchi and Luca Gianni) -- Beyond trastuzumab: Second generation targeted therapies for HER2--positive breast cancer (Flavio F. Solca, Guenther R. Adolf, Hilary Jones, Martina M. Uttenreuther-Fischer).
Electronic reproduction.
Keywords: Medicine; Oncology; Immunology; Electronic books